2021
DOI: 10.1089/whr.2021.0009
|View full text |Cite
|
Sign up to set email alerts
|

Provider Perspectives on Barriers and Facilitators to Postpartum Care for Low-Income Individuals

Abstract: Background: Recent paradigm shifts in postpartum care have conceptualized the ''fourth trimester'' as a critical transitional period requiring tailored, ongoing health care. However, this concept presents challenges for providers, especially in low-resource settings. Our objective was to understand providers' perspectives on challenges in postpartum care to highlight strategies for optimizing care. Methods: Focus groups were conducted using a semistructured interview guide to elicit perspectives on barriers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Barrier-free information sharing between different facilities or settings, regulation and optimizing of the primary care would improve the current situation. A previous study has also shown similar negative influence arising from lack of care continuity and lack of trust in providers of PPC [ 61 ].…”
Section: Discussionmentioning
confidence: 68%
“…Barrier-free information sharing between different facilities or settings, regulation and optimizing of the primary care would improve the current situation. A previous study has also shown similar negative influence arising from lack of care continuity and lack of trust in providers of PPC [ 61 ].…”
Section: Discussionmentioning
confidence: 68%
“…Although it is a challenging period for many, individuals with low income face additional barriers in acquiring critical health and social services. 22 , 25 Patient navigation in the obstetrical setting is a potential patient-centered solution to barriers encountered during prenatal and postnatal care. 17 , 18 , 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…15 A large proportion of racial and ethnic minority postpartum women, especially low-income women, face barriers such as housing insecurity, lack of transportation, and child-care concerns to name a few. 16,17 A first step in addressing this would be to implement routine screening for these barriers during our clinical visits so that we can identify women who need support. Broadening our collaboration with patient care navigators, community health workers, and social workers will be integral to addressing these barriers and coordinating comprehensive postpartum care.…”
Section: Strengthening Postpartum Carementioning
confidence: 99%